2015
DOI: 10.1002/cam4.548
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib for the treatment of advanced hepatocellular carcinoma with extrahepatic metastasis: a prospective multicenter cohort study

Abstract: Sorafenib, an oral multikinase inhibitor, is approved for advanced hepatocellular carcinoma (HCC) treatment. However, its therapeutic effect in advanced HCC patients with extrahepatic metastasis remains uncertain. This study aimed to prospectively assess the efficacy, safety, and survival risk factors and evaluate the prognostic impact of sorafenib treatment in advanced HCC patients with or without extrahepatic metastasis. Between May 2009 and March 2014, 312 consecutive advanced HCC patients who received sora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 32 publications
6
65
0
1
Order By: Relevance
“…Aino et al[32] have reported that local control of hepatic lesions contribute to better survival benefits, even for the patients with EHM. According to the report by Nakano et al[33, 34], advanced hepatic lesions, such as MVI, strongly correlate with poor survival and RR for treatments like sorafenib, which suggests that we need to develop an optimal multidisciplinary therapeutic strategy for advanced HCC to control local hepatic lesions. In this study, maximal RR and DCR of EBRT for MVI tumor thrombus were 55 and 85%, respectively, which suggests that the ability of local control of EBRT is extremely high.…”
Section: Discussionmentioning
confidence: 99%
“…Aino et al[32] have reported that local control of hepatic lesions contribute to better survival benefits, even for the patients with EHM. According to the report by Nakano et al[33, 34], advanced hepatic lesions, such as MVI, strongly correlate with poor survival and RR for treatments like sorafenib, which suggests that we need to develop an optimal multidisciplinary therapeutic strategy for advanced HCC to control local hepatic lesions. In this study, maximal RR and DCR of EBRT for MVI tumor thrombus were 55 and 85%, respectively, which suggests that the ability of local control of EBRT is extremely high.…”
Section: Discussionmentioning
confidence: 99%
“…Sorafenib is an effective and widely used molecular target drug in HCC [53][54][55][56][57]. Besides the classical pathway directly targeting HCC, sorafenib was found to mediate the antitumor effect via macrophages.…”
Section: Dusp1 and Cancer Molecular Target Drugsmentioning
confidence: 99%
“…Trastuzumab decreased DUSP1 which leads to the accumulation of phosphorylated active forms of JNK to enhance apoptotic induction. However, DUSP1 was somehow found to be increased in anti-HER2 therapyresistant cells and combined approaches interrupting both HER2 signaling and DUSP1 activity have proven even more successful [57].…”
Section: Dusp1 and Cancer Molecular Target Drugsmentioning
confidence: 99%
“…The landscape of systemic therapy for advanced HCC has changed with the advent of molecular-targeted therapy. Sorafenib, a relatively new molecular-targeted therapy for advanced HCC, was approved in Japan in May 2009 (11)(12)(13). Sorafenib is a multi-kinase inhibitor targeting the vascular endothelial growth factor receptor, platelet-derived growth factor receptor, and proto-oncoprotein c-Raf, among others (14,15).…”
Section: Introductionmentioning
confidence: 99%